Heparan Sulfate Proteoglycan Clustering in Wnt Signaling and Dispersal - Mii, Yusuke; Takada, Shinji (Frontiers in Cell and Developmental Biology, 2020)
Wnt, a family of secreted signal proteins, serves diverse functions in animal development, stem cell systems, and carcinogenesis. Although Wnt is generally considered a morphogen, the mechanism by which Wnt ligands disperse is still debated. Heparan sulfate proteoglycans (HSPGs) are extracellular regulators involved in Wnt ligand dispersal. Drosophila genetics have revealed that HSPGs participate in accumulation and transport of Wnt ligands. Based on these findings, a “restricted diffusion” model, in which Wnt ligands are gradually transferred by repetitive binding and dissociation to HSPGs, has been proposed. Nonetheless, we recently found that HSPGs are not uniformly distributed, but are locally clustered on cell surfaces in Xenopus embryos. HSPGs with N-sulfo-rich HS chains and those with N-acetyl-rich unmodified HS chains form different clusters. Furthermore, endogenous Wnt8 ligands are discretely accumulated in a punctate fashion, colocalized with the N-sulfo-rich clusters. Based on these lines of evidence, here we reconsider the classical view of morphogen spreading controlled by HSPGs.